Analisis Struktur dan Nilai Moral pada Naskah Drama Wanci Karya Ayi G. Sasmita (Indo-MathEdu Intellectuals Journal, 2024)
Analysis of Structure and Moral Values in the Script of the Drama Wanci by Ayi G. Sasmita. In this study, there are several problem formulations, namely how the structure and moral values appear in the script of the play Wanci by Ayi G. Sasmita. The purpose of this study is to describe the structure and moral values that appear in the script of the Wanci play. This drama script has noble values about life. This study applies a qualitative approach with a literature study method to analyze literary works. The main sources of data for this research are literary works and other sources that are reevan. Data analysis was carried out through qualitative data analysis, namely content analysis of literary works. The findings of this research are that the structure of the drama script "Wanci" refers to Waluyo's theory, which includes themes, story facts (plot, characters, and setting), and literary means (title, point of view, language style, symbolism, and irony). Meanwhile, the moral value in the drama script "Wanci" refers to theories that include the relationship between humans and themselves, the relationship between humans and other humans in the social sphere, and the relationship between humans and their God